Young Scientia Community and Pancasila Moral Integrity - Rahmawati, Ega (Universitas Negeri Semarang, 2015)
Pancasila is the ideology, guideline and basis of the Indonesian state. The five precepts of Pancasila are the embodiment of the basic values that come from real values in people's lives. Pancasila as a guideline for the community in carrying out an action and can be used as a rejection of values that are not in accordance with the Pancasila. In the development of today's society, the term millennial generation appears. Millennial generation is a generation born of the rapid development of Technology and Communication Sciences. Millennials include generation Y where in every life can not be separated from the influence of technology in various fields of life. But in reality, millennial geners in Indonesia are increasingly alarming. There are various problems facing the current millennial generation which are the challenges of the Pancasila in dealing with them. Such as the anti-social attitude, the influence of hoaxes, and the influence of hedonism on the millennial generation which is a deviation from the implementation of the Pancasila.